Education Policy Network Analysis in The Implementation of Student Exchange Activities in Indonesia - Arjanto, Paul; Senduk, Feibry Feronika Wiwenly; Sunandar, Asep; Sobri, Ahmad Yusuf (J-MPI (Jurnal Manajemen Pendidikan Islam), 2023)
This study aims to examine the literature related to the implementation of student exchange activities in the MBKM program at universities in Indonesia. Policy network analysis is used to analyze the implementation of student exchange policies in the MBKM program. The results of the study show that the roles of actors involved in policy networks who have an interest in and involvement in student exchange activities/programs include: 1) Directorate General of Higher Education, 2) sending universities, 3) receiving universities, 4) lecturers supervisor/lecturer in charge of the subject/mentor, 5) Independent Student Participants in the Exchange program. Each actor has played a role in accordance with their main duties and functions and collaborated with other actors so that the implementation of the Exchange activities Program goes according to standard operational guidelines.